1998
DOI: 10.1128/jb.180.15.3882-3890.1998
|View full text |Cite
|
Sign up to set email alerts
|

YscO of Yersinia pestis Is a Mobile Core Component of the Yop Secretion System

Abstract: The Yersinia pestis low-Ca2+ response stimulon is responsible for the temperature- and Ca2+-regulated expression and secretion of plasmid pCD1-encoded antihost proteins (V antigen and Yops). We have previously shown that lcrD, yscC, yscD,yscG, and yscR encode proteins that are essential for high-level expression and secretion of V antigen and Yops at 37°C in the absence of Ca2+. In this study, we characterized yscO of the Yop secretion (ysc) operon that contains yscN through yscU by determining the localizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 75 publications
(131 reference statements)
3
39
0
1
Order By: Relevance
“…2). As previously shown for mutants deficient in T3SA assembly (Jouihri et al, 2003), the needle component MxiH was not detected in the culture medium of the spa13 mutant (data not shown), consistent with a role of YscO-SpaM-Spa13 family members in T3SA assembly (Sasakawa et al, 1993;Collazo et al, 1995;Payne and Straley, 1998). To complement the spa13 mutant, we constructed plasmids pC78 carrying spa13a and spa13b with the wild-type slippage site and pC83 carrying spa13a and spa13b with a mutated site, such that transcriptional slippage can not occur and the sequence of the protein encoded by spa13a is unchanged.…”
Section: Transcriptional Slippage In Spa13 Is Required For T3sa Assemblysupporting
confidence: 89%
See 1 more Smart Citation
“…2). As previously shown for mutants deficient in T3SA assembly (Jouihri et al, 2003), the needle component MxiH was not detected in the culture medium of the spa13 mutant (data not shown), consistent with a role of YscO-SpaM-Spa13 family members in T3SA assembly (Sasakawa et al, 1993;Collazo et al, 1995;Payne and Straley, 1998). To complement the spa13 mutant, we constructed plasmids pC78 carrying spa13a and spa13b with the wild-type slippage site and pC83 carrying spa13a and spa13b with a mutated site, such that transcriptional slippage can not occur and the sequence of the protein encoded by spa13a is unchanged.…”
Section: Transcriptional Slippage In Spa13 Is Required For T3sa Assemblysupporting
confidence: 89%
“…1B). Moreover, the deduced product of spa13b (112 residues) is shorter than other members of the YscO-SpaM-Spa13 family (155 residues) (Sasakawa et al, 1993;Collazo et al, 1995;Payne and Straley, 1998). These observations suggested that Spa13 might be encoded by spa13a and spa13b.…”
Section: Spa13 Is Produced From Two Overlapping Orfsmentioning
confidence: 93%
“…Similarly, several components of the virulence-associated TTS and translocation machineries are also export substrates. YscO and YscP are members of two poorly conserved families of secretion components that are exported to an extracellular location (Payne and Straley, 1998;Stainier et al, 2000). YscX, which is essential for Yop secretion in the yersiniae, was recently demonstrated to interact with cytosolic YscY and to be exported in a TTS-dependent manner (Day and Plano, 2000).…”
Section: Tts Machinerymentioning
confidence: 99%
“…In Yersinia, besides the needle subunit YscF and the translocators at the tip of the needle (see Table 1), three proteins that are exported themselves, YscI, YscO and YscX, are essential for the final translocation of the effectors. YscI and YscO have been shown to be already required for the assembly of the needle, like related small proteins from other T3S systems (Payne and Straley, 1998;Kimbrough and Miller, 2000). YscI resembles MxiI (Shigella) and PrgJ (Salmonella) that have been assigned to form a rod structure extending the hollow needle at the centre of the basal body (Sukhan et al, 2003;Marlovits et al, 2004;Sal-Man et al, 2012).…”
Section: Introductionmentioning
confidence: 99%